2019
DOI: 10.1016/j.jcms.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interreader variability of orbital volume quantification using 3D computed tomography for reconstructed orbital fractures

Abstract: Management of orbital fractures continues to present some difficulties, particularly regarding the prediction of late complications. Radiographic assessment provides a detailed evaluation, but the results lack consistency to be considered a standard factor in the decision-making process. Studies focusing on reliability of post-operative imaging are lacking. Materials and methods: We performed a retrospective study using patients from a major trauma center with unilateral orbital floor fracture who underwent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…29 However, almost a perfect agreement of OV assessment between different readers using manual segmentation has been documented, which suggests that OVMs are reproducible and reliable. 30 Other scholars have suggested that the OV is susceptible to be overestimation (by between −1.8 mL and 2.6 mL) and should be interpreted with caution. 31 The OVR is the ratio between the traumatized orbit and the unaffected side: OVR (%) = (volume of the traumatized orbit/OV of unaffected orbit) x 100.…”
Section: To Predict Posttraumatic Enophthalmosmentioning
confidence: 99%
“…29 However, almost a perfect agreement of OV assessment between different readers using manual segmentation has been documented, which suggests that OVMs are reproducible and reliable. 30 Other scholars have suggested that the OV is susceptible to be overestimation (by between −1.8 mL and 2.6 mL) and should be interpreted with caution. 31 The OVR is the ratio between the traumatized orbit and the unaffected side: OVR (%) = (volume of the traumatized orbit/OV of unaffected orbit) x 100.…”
Section: To Predict Posttraumatic Enophthalmosmentioning
confidence: 99%
“…Visto isso, é válido enfatizar a necessidade de uma abordagem individual para cada paciente com fratura orbitária. O intuito da intervenção cirúrgica é a reconstrução anatômica da órbita, com acessos adequados e materiais reconstrutivos; enquanto que o objetivo do tratamento conservador é, caso seja indicado, observar sinais/sintomas como fatores predictivos para a evolução do paciente sem nenhuma sequela estética/funcional, evitando uma abordagem um pouco mais invasiva (Marano, et al, 2019;Oliveira, Câmara & Coelho, 2019).…”
Section: Resultsunclassified
“…The study of some of these was possible in the past only by gross observation, and often after the destruction or dissection of the bone (Rae & Koppe, 2004). The availability of virtual methods has facilitated a number of studies examining the sizes, shapes, relationships, functions and evolutionary implications of such cranial cavities and fossae (de Oliveira et al, 2019; Evteev et al, 2014; Fatterpekar et al, 2008; Hill & Richtsmeier, 2008; Landi et al, 2021; Márquez, 2008; Márquez, Pagano, Lawson, et al, 2014; Noback et al, 2011; Profico et al, 2020; Zollikofer & Weissmann, 2008). In particular, the human neurocranial cavity has been intensively studied, since its morphology closely reflects that of the brain and it is straightforward to create a virtual endocast that closely mirrors its general form and some specific aspects of brain anatomy (e.g.…”
Section: Introductionmentioning
confidence: 99%